Lactic Acidosis : A Poorly Understood Concept - Harrison Sanjay; Benziger Harrison (Journal of Glycomics And Metabolism, 2016)
Lactic acidosis is a condition commonly encountered in the hospital setting particularly in critically ill patients and is very often used as a diagnostic adjunct when encountering cases of ischaemia or other hypoperfusion states. Despite its use many clinicians have long forgotten the biochemical mechanisms that give rise to hyperlactataemia. One reason for this is because the basic science regarding lactate metabolism is taught in the early years of the medical undergraduate course, and unless one specialises in metabolic medicine, is unlikely to encounter it again. In this article we aim to elucidate the basic mechanisms of lactate metabolism and the accompanying acidosis, and illustrate various clinical settings that give rise to this biochemical abnormality.
Keywords: Hyperlactataemia